Factors influencing the formation of block copolymer-based supramolecular assemblies in bulk and thin films. (September 2020) - Deepthi, Krishnan; Stamm, Manfred; Gowd, E. Bhoje
Graphical abstract: Abstract: The factors that control the formation of supramolecular assemblies (SMAs) by hydrogen bonding using polystyrene- block -poly(4-vinyl pyridine) (PS- b -P4VP) and biphenyl systems containing different functionalities were investigated both in bulk as well as in thin films. 4-Hydroxybiphenyl (4HB) (hydroxyl functionalized), biphenyl-4-carboxylic acid (BPCA) (carboxyl functionalized) and 4′-hydroxy-4-biphenylcarboxylic acid (HBCA) (with both hydroxyl and carboxyl functionalities) were chosen as small molecules. Phase behavior of SMAs in bulk was studied by temperature-dependent wide-angle and small-angle X-ray scattering. All the SMAs showed the macrophase separation of small molecules in solvent casted samples. Heating or annealing above the glass transition temperature of block copolymers turned out to be a crucial factor in the effective formation of SMAs in the case of 4HB. On the other hand, SMAs formation is not that effective in the case of the carboxylic group-containing small molecules (BPCA and HBCA). Heating or annealing of as casted films above the melting temperature of small molecules leads to the homogeneous dispersion of BPCA and HBCA in SMAs due to the breakage of hydrogen-bonds. In thin films, SMAs formation by solvent vapor annealing is sensitive to the selectivity of solvents to constituted blocks and small molecules. Breaking of self-association of small molecules by heating above melting temperature of small molecules or annealing in a good solvent for both block copolymers and the small molecules is a key factor in the formation of SMAs in bulk and thin films. The present study provides a guideline for the basic design of effective SMAs using different kinds of small molecules, block copolymers and annealing conditions.